PROFIL SELF-DISCLOSURE PESERTA DIDIK SMA NEGERI DI KECAMATAN KALIDERES JAKARTA BARAT - Dyah Pratiwi; Rochani (STKIP Subang, 2026)
This study aims to determine the self-disclosure profile of public senior high school students in Kalideres District, West Jakarta. Self-disclosure is an essential foundation for adolescents to build healthy interpersonal relationships and obtain social support in the school environment. A descriptive quantitative research approach was employed in this study. The research population comprised all students in grades X, XI, and XII across SMAN 56, SMAN 84, SMAN 94, and SMAN 95 Jakarta, totaling 3,025 students. A sample of 353 students was determined using the Slovin formula and selected through proportionate stratified random sampling. Data collection was conducted by distributing the Jourard Self-disclosure Questionnaire (JSDQ) instrument, which covers six aspects: attitudes and opinions, tastes and interests, work or education, money, personality, and body. Data analysis utilized descriptive statistical techniques including score categorization, percentages, and means processed via IBM SPSS Statistics version 25. The results indicated that the self-disclosure profile of public senior high school students in Kalideres District generally falls into the moderate category, with a dominant percentage of 67.1% (239 students). Meanwhile, 16.9% (60 students) were in the high category and 16.0% (57 students) were in the low category. Analysis by aspect revealed that all indicators were dominated by the moderate category, with tastes and interests achieving the highest level of openness. These findings indicate that most students possess a fairly good ability to open up but remain selective based on emotional comfort and trust. The results of this study are expected to serve as a baseline for guidance and counseling teachers in designing comprehensive service programs to optimize students' interpersonal communication skills.